Challenges of the Sandwich Generation: Stress and coping strategy of the multigenerational care - Sudarji, Shanty; Panggabean, Hana; Marta, Rustono Farady (Universitas Muhammadiyah Surakarta, 2022)
Abstract. The Sandwich Generation is defined as those in multigenerational care positions and caregivers for children and parents or in-laws. They are often found in an extended families in Indonesia. Multigenerational parenting carried out by the Sandwich Generation can pose various challenges and problems, especially for Sandwich Generation working females, who must juggle their parenting loads with workplace demands. The Sandwich Generation is at risk for various mental health problems, including stress, depression, and anxiety. The purpose of this study is to describe the stress and coping strategies of the Sandwich Generation. The participants were 12 Sandwich Generation working females a mean age of 36. We applied a phenomenological qualitative approach with Interviews and Focus Group Discussions to collect our data. The result showed that stress occurs mainly in situations when parenting demands arise simultaneously, when both children and parents simultaneously need attention. Stress that appears generally has more impact on the emotional aspects of participants rather than on the physical one, such as feelings of sadness, guilt, and unstable emotions, and in terms of cognitive, forgetfulness, loss of concentration, and overthinking. Coping strategies used by the Sandwich Generation are emotionfocused coping strategies and problem-focused coping strategies. Emotion-focused coping strategies revealed distancing, escape-avoidance, accepting responsibility, self-control, and seeking emotional social support. We found only three problem-focused coping strategies: confrontative coping, seeking informational support, and planful problem-solving.Keywords: sandwich generation; stress; coping strategies